The Collembola of northern Victoria Land (Antarctica): Distribution and ecological remarks - FRATI, FRANCESCO; FANCIULLI, PIETRO PAOLO; CARAPELLI, ANTONIO; DALLAI, ROMANO (1997)
Three species of Collembola were found in a detailed survey of the coastal area of northern Victoria Land. The three species showed differences in distribution and abundance but appeared to have the same ecological requirements. The presence of deglaciated soil and of vegetation, and the availability of water are critical for the development of collembolan commuities. A preliminary screening of genetic variability suggests that populations of the isotomid species Gressittacantha terranova are quite variable. Although not conclusive, these results suggest a promising approach to study the evolution of populations of soil arthropods in Antarctica